Glass-ceramics and preparation method thereof
By adjusting the components and preparation process of the crystallized glass, the existing crystallized glass raw materials have been solved, and the crystallized glass with high transmittance and mechanical properties have been achieved to meet the application needs of cover glass.
Patent Information
- Application Number
- CN202310754788.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-06-26
AI Technical Summary
While improving optical and mechanical properties of existing microcrystalline glasses, the raw material cost is high and the crystallinity is low, and cannot meet the transmittance and mechanical properties requirements of cover glass.
A microcrystalline glass is provided, and its components include SiO2 36% to 55%, Al2O3 25% to 35%, Li2O 0 to 4.8%, Na2O 4.2 to 14%, K2O 3.02 to 5%, TiO2 1 to 6%, ZrO2 1% to 3.9% and P2O5 3% to 8%. Through specific heat treatment and chemical reinforcement processes, microcrystalline glass with high transmittance and mechanical properties is prepared.
It achieves the improvement of the transmittance and mechanical properties of microcrystalline glass while ensuring low raw material costs, meets the application requirements of cover glass, and further improves the mechanical impact resistance of glass through chemical reinforcement.
Smart Images

Figure BDA0004302275040000101 
Figure BDA0004302275040000111 
Figure BDA0004302275040000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass production and manufacturing, and in particular to a microcrystalline glass and a preparation method thereof. Background Art
[0002] The development of the electronic information industry has driven the popularization and popularity of electronic terminals such as smart phones and tablets. The demand for cover glass such as mobile phone, tablet screen cover and laptop screen protector cover is also growing, and the cover glass used in the above scenarios needs to have high optical and mechanical properties.
[0003] The performance improvement of traditional glass has reached its limit, but it still cannot meet market demand. As a new type of cover material, microcrystalline glass can use the crystals in the glass to effectively improve the optical and mechanical properties of the glass. Traditional microcrystalline glass is mainly lithium aluminum silicon system, but the cost of lithium raw materials is high, which limits its production and application. Microcrystalline glass of magnesium aluminum silicon system has the problems of low crystallinity and inability to be effectively strengthened.
[0004] Therefore, there is an urgent need for a microcrystalline glass that can meet the transmittance and mechanical property requirements of the cover glass and has low raw material costs. Summary of the invention
[0005] Based on this, it is necessary to provide a microcrystalline glass and a preparation method thereof with high transmittance and mechanical properties and low cost.
[0006] In one aspect of the present application, a microcrystalline glass is provided. The components of the microcrystalline glass include, by mass fraction, 36% to 55% SiO2, 25% to 35% Al2O3, 0% to 4.8% Li2O, 4.2% to 14% Na2O, 3.02% to 5% K2O, 1% to 6% TiO2, 1% to 3.9% ZrO2 and 3% to 8% P2O5.
[0007] In one embodiment, the components of the microcrystalline glass include, by mass fraction, SiO2 40% to 50%, Al2O3 26% to 35%, Li2O 0.1 to 3%, Na2O 5 to 12%, K2O 3.7 to 5%, TiO2 1 to 5%, ZrO2 3% to 3.9% and P2O5 4% to 6%.
[0008] In one embodiment, the crystal phase of the microcrystalline glass includes a first crystal phase and a second crystal phase; the first crystal phase is one or more of eucryptite, sodium nepheline and natural nepheline, and the second crystal phase is one or more of spodumene, spodumene solid solution, quartz, quartz solid solution, petalite and albite.
[0009] In one embodiment, the sum of the mass fractions of TiO2, ZrO2 and P2O5 in the components of the glass-ceramics is 5% to 12% by mass; and / or
[0010] In the components of the microcrystalline glass, the sum of the mass fractions of Li2O, Na2O and K2O is 7.23% to 18%.
[0011] In one of the embodiments, in the components of the microcrystalline glass, the ratio of TiO2+ZrO2+P2O5 / SiO2+Al2O3 is 0.058 to 0.18 by mass fraction.
[0012] In another aspect of the present application, a method for preparing the microcrystalline glass is provided, comprising the following steps:
[0013] Weighing raw materials according to the mixing ratio of the components contained in the microcrystalline glass, mixing the raw materials, heating them, and preparing a molten liquid;
[0014] homogenizing, shaping, and annealing the molten liquid to prepare a precursor glass;
[0015] The precursor glass is heat-treated to prepare the glass-ceramics.
[0016] In one embodiment, the heating temperature is 1530°C to 1620°C, and the time is 4 to 10 hours; and / or the annealing temperature is 550°C to 630°C, and the time is 4 to 8 hours; and / or the heat treatment temperature is 550°C to 850°C, and the time is 1 to 12 hours.
[0017] In another aspect of the present application, a strengthened glass is provided, which is prepared by chemically strengthening the microcrystalline glass.
[0018] In one embodiment, the chemical strengthening comprises the following steps:
[0019] The microcrystalline glass is placed in a mixed molten salt of sodium nitrate and potassium nitrate, and kept warm for 2 to 12 hours at a temperature of 370° C. to 490° C. to perform a first ion exchange, wherein the mass ratio of the sodium nitrate to the potassium nitrate is 90:10 to 20:80;
[0020] The microcrystalline glass after the first ion exchange is placed in a mixed molten salt of sodium nitrate and potassium nitrate, and kept warm for 0.5 to 8 hours at a temperature of 370° C. to 490° C. to perform a second ion exchange, wherein the mass ratio of the sodium nitrate to the potassium nitrate is 40:60 to 0:100.
[0021] In another aspect of the present application, an electronic screen is provided, comprising the tempered glass.
[0022] The microcrystalline glass with the mass percentage of the components in the present application has high transmittance and mechanical properties, can meet the applicable requirements of cover glass, and has low raw material costs, which is conducive to industrial production. DETAILED DESCRIPTION
[0023] In order to facilitate understanding of the present application, the present application will be described in more detail below. Preferred embodiments of the present application are provided hereinafter. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0025] The following is a detailed description of a glass-ceramic and a preparation method thereof provided in the present application.
[0026] In one aspect of the present application, a microcrystalline glass is provided. The components of the microcrystalline glass include, by mass fraction, 36% to 55% SiO2, 25% to 35% Al2O3, 0% to 4.8% Li2O, 4.2% to 14% Na2O, 3.02% to 5% K2O, 1% to 6% TiO2, 1% to 3.9% ZrO2 and 3% to 8% P2O5.
[0027] Silicon dioxide (SiO2) is the main component of the glass network skeleton. SiO2 can improve the mechanical strength, chemical stability and thermal stability of glass. SiO2 is also the main component of petalite, spodumene, lithium metasilicate, lithium disilicate, lithium phosphate, and quartz crystals. The type of crystal can be adjusted by controlling the content of SiO2. For example, a precursor glass with a higher SiO2 content is more likely to produce a higher proportion of quartz crystals after heat treatment. When the SiO2 content is lower than 36%, the network integrity of the glass melt decreases and the stability decreases; when the SiO2 content exceeds 55%, the high-temperature viscosity of the glass increases, which is not conducive to the industrial production of the composition. Therefore, in the components of the microcrystalline glass, the mass fraction of SiO2 is 36% to 55%, and the mass fraction of SiO2 includes but is not limited to: 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55% or in the range of any of the above values.
[0028] Alumina (Al2O3) can make the glass network structure more complete and improve the chemical stability, elastic modulus and hardness of the glass. 3+ [AlO4] tetrahedrons are formed, and larger void channels are formed in the network structure of the glass, which is beneficial to alkali metal ion exchange to obtain greater surface compressive stress and stress layer depth. Al2O3 is the main component of petalite and spodumene crystals. The proportion of lithium silicate can be reduced by increasing the content of Al2O3. The size of the three-dimensional skeleton structure of the microcrystalline glass can also be adjusted by adjusting the content of Al2O3. In the components of the microcrystalline glass, the mass fraction of Al2O3 is 25% to 35%, including but not limited to 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or any of the above values.
[0029] Lithium oxide (Li2O) is an ideal flux in glass components. + The polarization characteristics of Li can effectively reduce the high temperature viscosity at high temperature and improve the melting and forming properties of glass. + It is beneficial to the secondary chemical strengthening of glass and improves its strength. The present invention uses a mixed molten salt of NaNO3 and KNO3 in the strengthening process to + With Na in molten salt + Ion exchange can increase the depth of the compressive stress layer in a shorter time, making the glass have better mechanical impact resistance. In the components of the microcrystalline glass, the mass percentage of Li2O is 0% to 4.8%, including but not limited to 0.2%, 1%, 1.6%, 2%, 2.8%, 3.2%, 3%, 3.6%, 4.1%, 4.3%, 4.5%, 4.8% or any of the above values, preferably 0.1% to 3%. If its mass percentage is higher than 4.8%, the number of ions inside the glass is too much, resulting in a significant increase in the glass expansion coefficient, and the glass has a high tendency to crystallize, and the probability of glass forming stone defects is significantly increased.
[0030] Sodium oxide (Na2O) acts as a network exosome in glass, which has the effect of reducing the melting temperature of the precursor glass. It can also be used to control the viscosity of the glass during the crystallization process, inhibit deformation or adverse thermal expansion, but too high a content of Na2O will reduce the chemical stability of the glass. Na2O and K2O do not participate in crystallization, but can promote the crystallization of lithium metasilicate and inhibit the crystallization of petalite, spodumene and lithium disilicate. Excessive Na2O may cause the three-dimensional skeleton structure of the crystal to wrap around the residual glass phase, hindering the exchange of large ions in the molten salt to a deeper depth. In the components of the microcrystalline glass, the mass percentage of Na2O is 4.2% to 14%, including but not limited to 4.2%, 4.8%, 5.3%, 6.6%, 7.6%, 8.7%, 9.2%, 10.3%, 11.2%, 12.6%, 13.5%, 14% or any of the above values.
[0031] Potassium oxide (K2O) has similar properties to Na2O. Adding K2O and Na2O simultaneously can produce a mixed alkali effect, improve the high-temperature melting and clarification properties of the glass, and promote chemical strengthening. However, when the content of K2O is too high, the ion exchange capacity of the glass decreases. In the components of the microcrystalline glass, the mass percentage of K2O is 3.02% to 5%, including but not limited to 3.1%, 3.2%, 3.5%, 4%, 4.2%, 5% or any of the above values.
[0032] Titanium oxide (TiO2) is a component that helps lower the melting temperature of glass and improves chemical stability. Introducing 1% to 6% TiO2 into the components of glass-ceramics can make the glass crystallization process easier to control. Specifically, in the components of the glass-ceramics, the mass percentage of TiO2 includes but is not limited to 1%, 2.1%, 3.2%, 3.6%, 4.1%, 4.6%, 5.1%, 5.7%, 6% or any of the above values.
[0033] Zirconium oxide (ZrO2) can enhance the ion exchange power of glass, and at the same time improve the hardness and Young's modulus of glass, and improve the weather resistance and stability of glass, but too much ZrO2 will significantly increase the melting temperature of glass. Therefore, in the composition of the microcrystalline glass, the mass fraction of ZrO2 is 1% to 3.9%, including but not limited to 1%, 2.5%, 2.6%, 3%, 3.7%, 3.8%, 3.9% or any of the above values.
[0034] Phosphorus oxide (P2O5) has the function of fluxing and promoting glass phase separation. The glass transition temperature and crystallization temperature can also be controlled by adjusting the content of P2O5. P2O5 can lead to the formation of phosphate crystals and increase the proportion of phosphate crystals. P2O5 can increase the overall proportion of crystals in glass ceramics, control the change of grain size, and promote the formation of a three-dimensional skeleton structure of the crystal. It also promotes the residual glass phase to present a three-dimensional interconnected structure and increase the depth of ion exchange. In the components of the microcrystalline glass, the mass fraction of P2O5 is 3% to 8%, including but not limited to 3%, 3.4%, 4.5%, 5.6%, 6.7%, 7.2%, 7.9%, 8% or any of the above values.
[0035] Furthermore, the components of the microcrystalline glass provided in the present application do not include Sb2O3 or As2O3.
[0036] Furthermore, the components of the glass-ceramics provided in the present application do not include clarifiers such as Sb2O3 or As2O3.
[0037] Furthermore, the components of the microcrystalline glass provided in the present application do not include B2O3, which can reduce costs while reducing environmental pollution.
[0038] In one example, the components of the microcrystalline glass include, by mass fraction, SiO2 40% to 50%, Al2O3 26% to 35%, Li2O 0.1 to 3%, Na2O 5 to 12%, K2O 3.7 to 5%, TiO2 1 to 5%, ZrO2 3% to 3.9% and P2O5 4% to 6%.
[0039] In one example, the crystal phase of the microcrystalline glass includes a first crystal phase and a second crystal phase. Further, the first crystal phase includes one or more of eucryptite, sodium nepheline and natural nepheline.
[0040] Furthermore, the second crystalline phase includes one or more of spodumene, spodumene solid solution, quartz, quartz solid solution, petalite and albite.
[0041] In one example, in terms of mass fraction, the sum of the mass fractions of TiO2, ZrO2 and P2O5 in the components of the microcrystalline glass is 5% to 12%.
[0042] Furthermore, in the components of the microcrystalline glass, TiO2, ZrO2 and P2O5 are used as composite nucleating agents. In the nucleation process, the field strength of phosphorus oxide itself is relatively high, which easily causes microphase separation and induces crystallization; it also attracts titanium ions and zirconium ions to aggregate, and promotes crystallization through the nucleation-growth process. Specifically, the sum of the mass fractions of TiO2, ZrO2 and P2O5 can be 5%, 6%, 7%, 8%, 9%, 10%, 11% or 12%.
[0043] In one example, in terms of mass fraction, the sum of the mass fractions of Li2O, Na2O and K2O in the components of the microcrystalline glass is 7.23% to 18%. Specifically, the sum of the mass fractions of Li2O, Na2O and K2O can be 7.3%, 7.5%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17% or 18%.
[0044] In one example, in terms of mass fraction, the ratio of TiO2+ZrO2+P2O5 / SiO2+Al2O3 in the components of the microcrystalline glass is 0.058-0.18. Controlling the ratio within the above range can avoid abnormal grain growth caused by too high or too low a ratio, which in turn affects the transparency and mechanical properties of the glass. When the ratio is within the above range, it is easy to control the grain size, and a uniform grain size is conducive to strengthening, so that glass with better performance can be obtained. Specifically, in the components of the microcrystalline glass, the ratio of TiO2+ZrO2+P2O5 / SiO2+Al2O3 can be 0.058, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17 or 0.18.
[0045] In another aspect of the present application, a method for preparing the microcrystalline glass is provided, comprising the following steps:
[0046] S110: weighing raw materials according to the mixing ratio of each component contained in the microcrystalline glass, mixing the raw materials, heating them, and preparing them into a molten liquid.
[0047] In one example, the heating temperature is 1530° C. to 1620° C., and the heating time is 4 to 10 hours.
[0048] S120: homogenizing, shaping, and annealing the molten liquid to prepare a precursor glass.
[0049] In one example, the annealing temperature is 550° C. to 630° C., and the time is 4 to 8 hours.
[0050] S130: heat-treating the precursor glass to prepare the glass-ceramics.
[0051] In one example, the heat treatment is performed at a temperature of 550° C. to 850° C. for a time of 1 to 12 hours.
[0052] Furthermore, the heat treatment step includes a first heat treatment step and a second heat treatment step, the first heat treatment step is: keeping warm at a temperature of 550°C to 720°C for 4 to 10 hours, and the second heat treatment step is: keeping warm at a temperature of 700°C to 850°C for 1 to 4 hours.
[0053] It should be noted that the molding method is not limited, and in the case of a large output, it can be any one of the float method, overflow method, down-draw method, etc. The method provided in the example of this application is only an example and is not limited to this method.
[0054] In another aspect of the present application, a strengthened glass is provided, which is obtained by chemically strengthening the microcrystalline glass.
[0055] In one example, the chemical strengthening comprises the following steps:
[0056] S110: placing the microcrystalline glass in a mixed molten salt of sodium nitrate and potassium nitrate, keeping the temperature at 370°C to 490°C for 2 to 12 hours, and performing a first ion exchange, wherein the mass ratio of the sodium nitrate to the potassium nitrate is 90:10 to 20:80. Specifically, the temperature of the first ion exchange may be 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C or 490°C. The mass ratio of the sodium nitrate to the potassium nitrate in the first ion exchange may be 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70 or 20:80.
[0057] S120: placing the glass-ceramics after the first ion exchange in a mixed molten salt of sodium nitrate and potassium nitrate, keeping the temperature at 370°C to 490°C for 0.5 to 8 hours, and performing a second ion exchange, wherein the mass ratio of the sodium nitrate to the potassium nitrate is 40:60 to 0:100. Specifically, the temperature of the second ion exchange may be 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C or 490°C. The mass ratio of the sodium nitrate to the potassium nitrate of the second ion exchange may be 40:60, 30:70, 20:80, 10:90 or 0:100.
[0058] The preparation method of the tempered glass is simple and easy to operate, can effectively reduce costs, and the crystal growth process is controllable without problems such as abnormal grain growth. The tempered glass obtained by the preparation method has high hardness and transmittance, and can meet the use requirements of cover glass.
[0059] In one example, the transmittance of the tempered glass in the range of 380nm to 800nm is 80.4% to 91.9%. Specifically, the transmittance of the tempered glass in the range of 380nm to 800nm can be 80.4%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 91.9% or any range of the above values.
[0060] In one example, the Vickers hardness of the tempered glass is 663 MPa to 798 MPa. Specifically, the Vickers hardness of the tempered glass may be 663 MPa, 670 MPa, 680 MPa, 690 MPa, 700 MPa, 710 MPa, 720 MPa, 730 MPa, 740 MPa, 750 MPa, 760 MPa, 770 MPa, 780 MPa, 790 MPa, 798 MPa or any range thereof.
[0061] In one example, the stress intensity of the tempered glass is 1455 MPa to 1554 MPa. Specifically, the stress intensity of the tempered glass may be 1455 MPa, 1460 MPa, 1470 MPa, 1480 MPa, 1490 MPa, 1500 MPa, 1510 MPa, 1520 MPa, 1530 MPa, 1540 MPa, 1550 MPa, 1554 MPa or any range thereof.
[0062] In one example, the stress layer depth DOL of the strengthened glass is 32 μm to 47 μm. Specifically, the stress layer depth DOL of the strengthened glass can be 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, 40 μm, 41 μm, 42 μm, 43 μm, 44 μm, 45 μm, 46 μm, 47 μm or any range thereof.
[0063] In one example, the depth DOL_0 of the strengthened glass at which the stress value is 0 is 81 μm to 128 μm. Specifically, the depth DOL_0 of the strengthened glass at which the stress value is 0 can be 81 μm, 82 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 128 μm, or any range of the above values.
[0064] In another aspect of the present application, an electronic screen is provided, comprising the microcrystalline glass or the tempered glass.
[0065] In one example, the method for preparing the tempered glass comprises the following steps:
[0066] (1) weighing raw materials according to the above-mentioned components of the glass-ceramics and mixing them evenly;
[0067] (2) placing the mixed raw materials in a platinum or alumina crucible, melting them at a temperature of 1530° C. to 1620° C., and keeping the temperature for 4 to 10 hours to prepare a molten liquid;
[0068] (3) homogenizing and casting the molten liquid, and then annealing at a temperature of 550° C. to 630° C. for 4 to 8 hours to prepare a precursor glass;
[0069] (4) placing the precursor glass into a muffle furnace and keeping it at a temperature of 550° C. to 850° C. for 1 to 12 hours to prepare the microcrystalline glass;
[0070] (5) cutting the above-mentioned microcrystalline glass into glass sheets with a thickness of 0.7 mm to 0.8 mm, and then grinding and polishing to obtain glass sheets with a thickness of 0.5 mm to 0.6 mm;
[0071] (6) placing the glass flakes in a mixed molten salt of sodium nitrate and potassium nitrate at a temperature of 370° C. to 490° C. for 2 to 12 hours to perform a first ion exchange, wherein the mass ratio of the sodium nitrate to the potassium nitrate is 90:10 to 20:80;
[0072] (7) placing the glass sheet after the first ion exchange in a mixed molten salt of sodium nitrate and potassium nitrate at a temperature of 370° C. to 490° C. for 0.5 to 8 hours, and performing a second ion exchange, wherein the mass ratio of the sodium nitrate to the potassium nitrate is 40:60 to 0:100, to obtain a strengthened glass.
[0073] The physical and chemical properties of the above-mentioned glass-ceramics and tempered glass were tested.
[0074] The embodiments of the present invention and the comparative examples are tested for the Vickers hardness of the glass surface by using an INNOVA FALCON Vickers hardness tester in accordance with the GB / T4340 standard; the transmittance (i.e., visible light transmittance) in the wavelength range of 380 to 800 nm is tested by using a GBC Cintra UV-visible spectrophotometer in accordance with the GB / T 40415 standard; the surface compressive stress and the stress layer depth are tested by using an FSM 600LE in accordance with the standards GB / T18144-2008 and ASTM1422C-99; and the grain size of the glass is tested by a FEI Quanta scanning electron microscope (SEM).
[0075] It can be understood that the above-mentioned test methods and test equipment are commonly used methods for evaluating glass-related properties in the industry. They are only a means to characterize or evaluate the technical scheme and technical effects of the present invention. Other test methods and test equipment may also be used without affecting the final results.
[0076] The following are specific embodiments.
[0077] Examples 1 to 50 and Comparative Examples 1 to 10
[0078] The preparation process of the glass-ceramics and tempered glass provided in Examples 1 to 50 and Comparative Examples 1 to 10 is as follows:
[0079] (1) Weigh the raw materials according to the mass percentage of each component in Table 1 and mix them evenly;
[0080] (2) placing the mixed raw materials in a platinum or alumina crucible, melting them at a temperature of 1530° C. to 1620° C., and keeping the temperature for 4 to 10 hours to prepare a molten liquid;
[0081] (3) homogenizing and casting the molten liquid, and then annealing at a temperature of 550° C. to 630° C. for 4 to 8 hours to prepare a precursor glass;
[0082] (4) placing the precursor glass in a muffle furnace, keeping it at a temperature of 550° C. to 720° C. for 4 to 10 hours, performing a first heat treatment, and then keeping it at a temperature of 700° C. to 850° C. for 1 to 4 hours, performing a second heat treatment, to obtain a microcrystalline glass;
[0083] (5) cutting the above-mentioned microcrystalline glass into glass sheets with a thickness of 0.8 mm, and then grinding and polishing to obtain glass sheets with a thickness of 0.6 mm;
[0084] (6) placing the glass sheet in a mixed molten salt of sodium nitrate and potassium nitrate at a temperature of 370° C. to 490° C. for 2 to 12 hours to perform a first ion exchange;
[0085] (7) The glass sheet after the first ion exchange is placed in a mixed molten salt of sodium nitrate and potassium nitrate at a temperature of 370° C. to 490° C. for 0.5 to 8 hours, and a second ion exchange is performed to obtain a strengthened glass.
[0086] The specific temperature and time during the preparation process are shown in Table 2.
[0087] Table 1 Ingredients
[0088]
[0089]
[0090]
[0091] Table 2 Heat treatment conditions and chemical strengthening conditions
[0092]
[0093]
[0094]
[0095]
[0096]
[0097]
[0098] The tempered glasses prepared in Examples 1 to 50 and Comparative Examples 1 to 10 were tested. The test results are shown in Table 3.
[0099] Table 3 Tempered glass performance test
[0100]
[0101]
[0102]
[0103]
[0104]
[0105] In comparative example 1, the content of silicon dioxide is too little, the content of aluminum oxide is high, and the precursor glass is not easy to form. The crystal content in the microcrystalline glass formed after heat treatment is low, and the grain size is very small, resulting in the low Vickers hardness, surface compressive stress and stress depth of the glass after chemical strengthening. Comparative example 2 contains too much aluminum oxide content, which brings certain difficulties to melting, and also causes abnormal growth of crystals in the glass during crystallization, affecting the transparency and hardness of the glass, making it lower than the use requirements. The aluminum oxide content in comparative example 3 is too little, making it difficult to form crystals in the glass, and the crystallinity is low, resulting in the prepared glass. Although the transmittance can meet the requirements, the hardness and surface compressive stress are low, which cannot meet the use requirements. Comparative example 4 uses too much lithium oxide raw material, although it can effectively promote the formation of lithium metasilicate in the glass, which is beneficial to the performance of the glass, the introduction of too much lithium oxide will cause the cost of the raw materials to rise suddenly, and the cost requirements cannot be met. In comparative example 5, the sodium oxide content is low, which increases the difficulty of melting on the one hand, and also causes the main crystal phase sodium nepheline to be difficult to form due to the lack of sodium oxide. The surface compressive stress and stress depth of the glass are low after chemical strengthening treatment. In Comparative Example 6, the sodium oxide content is too high, which causes the structure of the glass itself to become loose, and then the hardness of the glass after crystallization and chemical strengthening is reduced. In addition, too much sodium oxide also causes the crystals in the glass to grow abnormally, reducing the transmittance of the glass. In Comparative Example 7, the titanium oxide content is too low, causing the crystals to form mainly on the surface of the glass. After processing, the crystal content in the glass is greatly reduced, resulting in a decrease in the hardness of the glass itself; at the same time, the surface crystals hinder the ion exchange during the chemical strengthening process, resulting in a decrease in the surface stress of the glass and a decrease in the ion exchange depth, which cannot meet the performance requirements. In Comparative Example 8, the titanium oxide content is too high, causing the molten glass to turn yellow and black. After heat treatment and chemical strengthening, the obtained glass still has a darker color, and the transmittance is low and cannot meet the use requirements. In Comparative Example 9, the zirconium oxide content is too high, resulting in a significant increase in the difficulty of glass melting. The glass contains white refractory materials and a large number of bubbles, which seriously affects the quality of the prepared glass. The crystals in the prepared microcrystalline glass also grow abnormally, greatly reducing the usability of the glass. The excessive phosphorus oxide content in Comparative Example 10 also increases the viscosity and difficulty of glass melting, affects the quality of the glass body, and makes subsequent treatment and processing impossible.
[0106] The technical features of the comparative examples described above can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the comparative examples described above are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0107] The comparative examples described above only express several embodiments of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A glass-ceramic, characterized in that: Measured by mass fraction, the components of the microcrystalline glass include SiO2 47.81%~55%, Al2O3 25%~28.34%, Li2O 0~4.8%, Na2O 4.3%~13.86%, K2O 3.02%~3.83%, TiO2 1%~3.13%, ZrO2 1%~2.2% and P2O5 3%~7%; and the ratio of TiO2+ZrO2+P2O5 / SiO2+Al2O3 is 0.082~0.
131.
2. The glass-ceramic according to claim 1, characterized in that: The mass fraction of Li2O is 0.1%~3%.
3. The glass-ceramic according to claim 1, characterized in that: The mass fraction of Na2O is 5%~12%.
4. The glass-ceramic according to claim 1, characterized in that: The mass fraction of P2O5 is 4%~6%.
5. The glass-ceramics according to any one of claims 1 to 4, characterized in that: The crystal phases of the microcrystalline glass include a first crystal phase and a second crystal phase; the first crystal phase is one or more of eucryptite, sodium nepheline and natural nepheline, and the second crystal phase is one or more of spodumene, spodumene solid solution, quartz, quartz solid solution, petalite and albite.
6. The glass-ceramic according to claim 1, characterized in that: In terms of mass fraction, the sum of the mass fractions of TiO2, ZrO2 and P2O5 in the components of the microcrystalline glass is 6.2%~10.58%.
7. The glass-ceramic according to claim 1, characterized in that: In terms of mass fraction, the sum of the mass fractions of Li2O, Na2O and K2O in the components of the microcrystalline glass is 7.58%~17.99%.
8. A method for preparing glass-ceramics according to any one of claims 1 to 7, characterized in that: The steps include: Weighing raw materials according to the mixing ratio of the components contained in the microcrystalline glass, mixing the raw materials, heating them, and preparing a molten liquid; homogenizing, shaping, and annealing the molten liquid to prepare a precursor glass; The precursor glass is heat-treated to prepare the glass-ceramics.
9. The method for preparing glass-ceramics according to claim 8, characterized in that: The heating temperature is 1530° C. to 1630° C., and the heating time is 4 to 10 hours.
10. The method for preparing glass-ceramics according to claim 8, characterized in that: The annealing temperature is 550° C. to 630° C., and the annealing time is 4 to 8 hours.
11. The method for preparing glass-ceramics according to claim 8, characterized in that: The heat treatment temperature is 550° C. to 850° C., and the time is 1 to 12 hours.
12. A tempered glass, characterized in that: The glass-ceramics is prepared by chemically strengthening the glass-ceramics described in any one of claims 1 to 7.
13. The tempered glass according to claim 12, wherein: The chemical strengthening comprises the following steps: The microcrystalline glass is placed in a mixed molten salt of sodium nitrate and potassium nitrate, and kept warm for 2 to 12 hours at a temperature of 370° C. to 490° C. to perform a first ion exchange, wherein the mass ratio of the sodium nitrate to the potassium nitrate is 90:10 to 20:80; The microcrystalline glass after the first ion exchange is placed in a mixed molten salt of sodium nitrate and potassium nitrate, and kept warm for 0.5 to 8 hours at a temperature of 370° C. to 490° C. to perform a second ion exchange, wherein the mass ratio of the sodium nitrate to the potassium nitrate is 40:60 to 0:
100.
14. An electronic screen, characterized in that: The tempered glass comprising the tempered glass according to any one of claims 12 to 13.
Citation Information
Patent Citations
Sodium aluminosilicate nanocrystalline transparent ceramic, preparation method thereof and product
CN111606572A
Glass ceramic, electronic equipment and preparation method of glass ceramic
CN113526872A
Glass ceramic containing hard stone crystal phase and glass ceramic product
CN115583798A
Glass ceramic and preparation method thereof
CN115893851A
Glass ceramic, preparation method thereof and glass product
CN116040946A